O método do gradiente conjugado de Hestenes e Stiefel modificado para otimização não-linear em alta dimensão - Lucas Almeida Portela (2022)
In this dissertation, we propose modifications in the Conjugate Gradient HS (Hestenes-Stiefel) method, naming it GC-HS*, for the purpose of making the method always well defined, regardless of the search line conditions that is being used, ensure that the sufficient descent condition is always attended and there is, under certain hypotheses, global convergence. Numerical results indicate that the proposed method is promising when compared to the methods: HS (Hestenes-Stiefel), PR (Polak-Ribière), DL (Dai-Liao) and GY (Gonglin Yuan).